SUSTAINABILITY WITH DIGITALISATION: GREEN ECONOMY SOLUTIONS IN ECONOMY 5.0 - Gunawan Widjaja (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This article discusses the role of digitalisation in supporting green economic sustainability in the era of Economy 5.0. Digitalisation, through the use of technologies such as the Internet of Things (IoT), big data and artificial intelligence (AI), offers solutions to optimise resources and reduce environmental impacts. In addition, digital platforms increase transparency and accuracy in sustainability monitoring, enabling stakeholders to make wiser data-driven decisions. The integration of digital technologies in sustainability strategies not only provides economic benefits, but also contributes to environmental protection, forming the basis for a greener and more responsible economic future.